Perbandingan Kebebasan Berijtihad dalam Tradisi Mazhab: Ushul Fikih dan Kontekstualisasi Ijtihad - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study compares the scope of freedom in exercising ijtihad across the four Sunni schools of Islamic jurisprudence through a comparative ushul al-fiqh perspective. It argues that freedom of ijtihad has never been absolute but has always been regulated by methodological frameworks shaped by each madhhab’s epistemological orientation. The Hanafi and Maliki schools emphasize substantive and contextual flexibility through rational reasoning and public interest, while the Shafi‘i and Hanbali schools prioritize methodological discipline and textual fidelity. The study concludes that these diverse models represent complementary approaches. In contemporary contexts, integrating their strengths enables responsible contextualization of ijtihad while preserving normative continuity and scholarly legitimacy. Keywords: Ijtihad, Madhhab, Ushul al-Fiqh